Theories of international relations - Chan, Stephen, 1949-; Moore, Cerwyn; Sage eBooks (London : SAGE, 2006)
These four volumes document international relations from realist theory and the development of pluralist approaches to the structuralist tradition stemming from Marx and Gramsci and reflexive theories.
v. 1. Approaches to international relations : realism -- v. 2. Approaches to international relations : pluralism -- v. 3. Approaches to international relations : structuralism -- v. 4. Contemporary reflexive approaches in international relations.
Specialized.
Description based on print version record.
Includes bibliographical references.
Keywords: International relations -- Philosophy; Electronic books